2019
DOI: 10.1007/s13202-019-0612-2
|View full text |Cite
|
Sign up to set email alerts
|

Waste bio materials based viscosity reduction and rheological properties of crude oil

Abstract: The effectiveness of using waste bio materials as viscosity reducing agents was investigated on light and heavy crude oils of Oman. The selected materials are fiber of palm tree, date palm kernel and walnut shell. The utilization of waste bio materials is not only considered as a cost effective, but, environmentally friendly and has less effect on crude oil processing as compared to that of chemical additives. In this study, special piping structure was constructed to measure flowabilty time of crude oil. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It was found that castor seed oil and jatropha seed oil were the most effective inhibitors, as they contain oxhydryl and π-bonds that can act as barriers to the formation of the waxy crystal network. The same conclusion was obtained for biowastes (palm tree fiber, date palm kernel, and walnut shell) . Azeem et al combined olive oil with pentadecane and VA to generate a composite polymer, which inhibited wax deposition through a cocrystallization mechanism, and lowered the pour point by 8 °C at 1000 ppm.…”
Section: Classification Of Pour Point Depressantsmentioning
confidence: 56%
See 1 more Smart Citation
“…It was found that castor seed oil and jatropha seed oil were the most effective inhibitors, as they contain oxhydryl and π-bonds that can act as barriers to the formation of the waxy crystal network. The same conclusion was obtained for biowastes (palm tree fiber, date palm kernel, and walnut shell) . Azeem et al combined olive oil with pentadecane and VA to generate a composite polymer, which inhibited wax deposition through a cocrystallization mechanism, and lowered the pour point by 8 °C at 1000 ppm.…”
Section: Classification Of Pour Point Depressantsmentioning
confidence: 56%
“…The same conclusion was obtained for biowastes (palm tree fiber, date palm kernel, and walnut shell). 141 Azeem et al 142 combined olive oil with pentadecane and VA to generate a composite polymer, which inhibited wax deposition through a cocrystallization mechanism, and lowered the pour point by 8 °C at 1000 ppm. Ragunathan et al 143 studied the inhibitory effect of palm oil compared with that of the commercial PPD ethylene-vinyl acetate (EVA) and reported that there was a critical concentration at which PPD decreased the pour point of crude oil.…”
Section: Green Pour Pointmentioning
confidence: 99%
“…Some prior experimental results , have suggested that the rheological behavior of heavy crude oil-in-water emulsions within a range of shear rates can be expressed by the following power-law equation: where τ is the shear stress, μ is the apparent viscosity, γ is the shear rate, K is the consistency index, and n is the flow behavior index. Meanwhile, the K value is the metric of fluid viscosity, with a higher viscosity meaning a larger K value. For a Newtonian fluid μ = K and n = 1.…”
Section: Resultsmentioning
confidence: 99%